Clinical and Epidemiological Study of Complicated Infection by Varicella-Zoster Virus in the Pediatric Age - Maia, Catarina (2015)
Introduction: In Portugal, the incidence of complicated infection by varicella-zoster virus is unknown. The purpose of this study was to describe the epidemiological and clinical features of complicated infection by varicella-zoster virus in children.Material and Methods: Retrospective review of the clinical files of patients admitted between January 1999 and July 2013, with a diagnosis of complicated varicella-zoster virus infection.Results: Ninety-four patients were hospitalized with complicated varicella-zoster virus infection, two of them by reactivation of latent infection. The median age was 38 (IQR 18 - 65) months. The most frequent types of complications were bacterial overinfection of the skin and subcutaneous cellular tissue (37.2%) and respiratory complications (24.5%). Other complications were neurologic complications (19.1%), gastrointestinal (9.6%), hematologic (5.3%) and osteoarticular (4.3%). In 38 patients invasive bacterial infections were diagnosed, with bacteremia in 6 patients. The median age was highest in the immunological complications compared with infectious complications. Neurological complications occurred mainly in healthy children, while infectious complications, including the invasive bacterial infections were more frequent in patients treated with ibuprofen and/or corticosteroids. The evolution was favorable in most cases.Discussion: The complications of varicella-zoster virus infection occurred mainly in pre-school age and in healthy children. Infectious complications, particularly respiratory complications and bacterial overinfection of the skin and subcutaneous cellular tissue, were the most frequent. There was association between infectious complications and previous therapy with ibuprofen and / or corticosteroids.Conclusion: Multicenter studies should be planned in order to optimize and adjust the vaccine strategies to our reality.